Qualitative risk assessments for the risk of introduction of HPAI H5N1 virus into Ethiopia - Siraw, Bewket; Chaka, Hassen (International Food Policy Research Institute, 2009)
As part of the DFID funded Pro-poor HPAI Risk Reduction Project, a qualitative risk assessment was conducted for risk questions, agreed during stakeholders workshop in September, 2008, related to introduction of highly pathogenic avian influenza (H5N1) virus into Ethiopia via wild birds trade transiting in the country and the transmission of the virus between large scale commercial and small scale commercial poultry farms. The principal risk questions were: * Risk question 1: Release assessment: What is the risk of introduction of HPAI (H5N1) via legal and illegal trade of wild birds transiting in Ethiopia? * Risk question 2: Exposure assessment: What is the probability that domestic poultry in Ethiopia become infected by H5N1 HPAI after the release of the virus by an infected traded wild bird transiting in Ethiopia? * Risk question 3: Consequence/transmission assessment: What is the risk of transmission of HPAI (H5N1) between large commercial poultry farms and small scale commercial poultry farms?